Motif dan warna dalam budaya Cina peranakan: Kajian kes ke atas kasut manik tradisional / Siti Khadijah Farhah Sulaiman - Siti Khadijah Farhah, Sulaiman (2019)
Malaysia is a unique country due to the variety of races and nationalities which consist of the Malays, Chinese, Indians, aboriginal people in the Peninsular of Sabah and Sarawak including the descendants of the Straits-born Chinese (Cina Peranakan). In order to complete the study, the Straits-born Chinese is selected as the main focus by investigating the art of beaded embroidery specifically on the Peranakan beaded shoes embarked within the culture. Nowadays, the beaded shoes concern more on geometrical and floral motive such as roses. However, the the motives such as human-like figure and fauna are no longer being made as the completion process is complicated. Despite that, those two motives were quite popular in the past as it portrays their own meanings. Apart from that, the objective of the study is to identify and analyse the motives and colours used on the beaded shoes as well as the influential value of the design. Furthermore, the data of the research are collected via observations, field study, documentation analysis on the images and the motives used towards the beaded shoes for further classification and investigation. As a result, the motives used on the beaded shoes are influenced by three cultures which are the Chinese, Malays and British. The fusion of these cultural elements made the beaded shoes unique and renowned its title as one of the historical shoes in Malaysia. On top of that, the beaded shoes are also well-known in Nanyang region (South China Sea); Malacca, Penang and Singapore.